Surgical Care under COVID-19 Pandemic Conditions (Literature Review) - M. V. Timerbulatov; R. R. Garaev; Sh. V. Timerbulatov; A. A. Bakirov; A. R. Gafarova (Креативная хирургия и онкология)
Since March 2020, when COVID-19 pandemic was declared by WHO, the new coronavirus infection has spread widely around the world, claiming many lives and destroying the economies, social structures, and various aspects of people’s lives. The pandemic has had a major impact on health facilities, including the surgical service. The healthcare system had to completely reorganize its methods of work. The need to deploy a significant number of infectious disease beds necessitated the convertion of many medical organizations into Covid hospitals, with a reduction in surgical units and beds. The scheduled surgical operations were therefore cancelled and postponed. Emergency surgical care was provided as needed, albeit in a reduced scope. The number of patients seeking emergency surgical care decreased mainly due to the fear of contracting COVID-19. The data show that there is a significant increase in the number of perioperative complications and mortality, especially in patients with acute surgical pathology and co-occurring COVID-19. The paper presents the data from professional literature on the peculiarities of surgical care in the context of the coronavirus pandemic, changes in a number of obligatory indicators of the quality of surgical care for patients.